THE IMPLEMENTATION OF CREATIVE PROBLEM SOLVING MODEL THROUGH PROCESS SKILL IN IMPROVING NATURAL SCIENCE LEARNING AT THE FIFTH GRADE OF SD NEGERI PLUMBON IN THE ACADEMIC YEAR OF 2014/2015 - Santi, Erlina Widia (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of Creative Problem Solving Model through Process Skill in Improving Natural Science Learning at the Fifth Grade of SD Negeri Plumbon in the Academic Year of 2014/2015. The objectives of this research are to describe the implementation steps of the Creative Problem Solving model through process skills, to improve Natural Science learning about the nature of light at the fifth grade, and to describe problems and solutions. This research is a collaborative Classroom Action Research (CAR). The research was conducted in three cycles consisting of planning, action, observation, and reflection in each cycle. The subjects were the fifth grade students of SD Negeri Plumbon totaling 22 students. The results of this research indicate that the implementation of the Creative Problem Solving model through process skill conducted with appropriate steps can improve Natural Science learning about the nature of light at the fifth grade students of SD Negeri Plumbon. Keywords: Creative Problem Solving, process skill, Natural Science